A Critique of the Thought of Modern American Orientalist Daniel Pipe - Nabiel Almusawa; Daud Rasyid; Zamaksyarif Abdul Majid; Muhibuddin Muhibuddin; Siti Nuri Nurhaidah; Siti Atieqoh (Yayasan Adra Karima Hubbi, 2025)
Background. This study critically examines the thoughts and perspectives of Daniel Pipes, a prominent modern American Orientalist known for his controversial views on Islam and the Muslim world. Purpose. The research analyzes the ideological underpinnings, methodological approaches, and political motivations that shape Pipes' discourse, particularly in post-9/11 Western perceptions of Islam. Method. Employing a critical discourse analysis framework and drawing upon postcolonial theory especially the insights of Edward Said this study identifies recurring patterns of essentialism, securitization, and cultural superiority in Pipes' writings. Results. The research argues that while Pipes positions himself as a scholar of political Islam, his works often blur the lines between academic inquiry and ideological advocacy. Conclusion. This critique contributes to broader discussions on Orientalism in contemporary settings and raises questions about the role of scholarship in perpetuating or challenging Islamophobic narratives in Western media and policy.